Effect of Green Marketing on Organizational Effectiveness of Jordanian Pharmaceutical Companies: The Mediating Role of Consumers’ Purchasing Behavior - AL-khawaldah, Reyad; Al Shoura, Mohammed (Jordan Journal of Business Administration, 2018)
This study aims to investigate the impact of green marketing dimensions (green product, green pricing, green promotion and green distribution) on organizational effectiveness, which includes the following four dimensions: growth, productivity, quality and employee satisfaction. Moreover, the study aims to identify the role of consumers’ purchasing behavior in order to improve the effect of green marketing on organizational effectiveness. The population of the study consisted of 16 Jordanian pharmatical companies. The sample consisted of 338 employees, who work in five Jordanian pharmaceutical companies. To achieve the study objectives, the descriptive analytical approach was adopted. Specifically, a survey (self-administrated questionnaire) was used as the main instrument to collect primary data. Several statistical techniques were used to analyze the data, which included descriptive statistics techniques, such as means and standard deviations, as well as analytical statistics techniques, which included simple and multiple regression and path analysis. Based on data analysis, the study revealed the following findings: * There was a positive impact of green marketing and its dimensions on organizational effectiveness. * There was a positive impact of green marketing on consumers’ purchasing behavior. Moreover, consumers’ purchasing behavior played a mediating role between green marketing and organizational effectiveness. Based on the study findings, a number of recommendations were suggested by the researchers as follows: Conducting comprehensive studies to examine parts of Jordanian pharmaceutical markets. Developing green products in the sampled companies in order to replace the traditional products and to maximize the benefits of green products. Increasing the commitment of target companies to enhance their ability to obtain quality and mark certificates. Finally, the major theoretical contribution of this paper lies in suppoting existing green marketing and organizational effectiveness theories with empirical evidence to explain the trilogy of relationships between green marketing, organizational effectiveness and consumers’ behavior in Jordanian pharmaceutical companies